Brakes and Levers to Reduce the Dependence on Imports in the Middle East-North Africa Region - (:unkn) unknown (My University, 2018)
The two reference scenarios and the results analysed previously rely on mere extensions of past trends and do not take into account possible breaks or ruptures other than those of accentuated climate change. Naturally, then, they are ‘scenarios of inaction’ which typically illustrate what might happen in the Middle East-North Africa region if ‘nothing is done’. We should first note that many of our hypotheses could be challenged by more marked changes, upwards or downwards, of certain contextual elements. Thus our demographic hypotheses, based on the UN’s median projection, do not take into account their inherent high levels of uncertainty. For this world region, the UN’s high and low projections reveal a potential variability of about +/−15% around the median projection. Similarly, changes in diets could be more marked. The Middle East has been falling behind in dietary terms over the past few decades and it could catch up. Or there could be an accentuation of Western characteristics in diets due to eating behaviour among the fringes of the region’s youngest population. In light of these further changes in various components of the agricultural and food system of the region, we must also consider the levers that regional governments could use to try to reduce the extreme dependence on agricultural imports towards which most countries in the Middle East-North Africa region are moving.
Keywords: African Research